APPLICATION OF COMBINED METHODS OF ASSESSMENT IN COMPETENCE MANAGEMENT SYSTEM OF INNOVATIVE COMPANIES - E. S. Fedorova; N. V. Lashmanova (Дискурс)
The competence management system is a part of corporate and functional strategies of innovative companies. The article presents the main features of this system, as well as the possibility of evaluating its elements. In order to control and reduce possible risks a conclusion is made about the need to develop an integrated model and the possibility to use statistical analysis techniques.